PHYSICO-CHEMICAL STUDIES ON ASSESSMENT OF GROUND WATER QUALITY NEAR COAL WASHERY OF DISTRICT BOKARO, JHARKHAND - ANJU KUMARI,; DR. RUPAM MALLIK, (The Bioscan, 2023)
In the present study an attempt has been made to assess the physico-chemical factors of two ground water samples of selected sampling sites viz, Dugda Ground water (GW1) Near Dugda coal washery and Bhojudih Ground water(GW2) near Bhojudih coal washery areas of district Bokaro, Jharkhand. Sampling sites are nearby Damodar River also. Samples were collected from hand pump (approx. 80 feet deep) on monthly basis from November 2020 to October 2021. A total of 9 parameters were taken into consideration for analysis. The average value of selected parameters of Dugda Ground water and Bhojudih Ground water , the Temperature was 21.300C-20.500C, pH 6.97-7.04,Elecrical Conductivity (EC) 778.25-886.83μs/cm, Dissolved Oxygen (DO) 2.404-3.099 mg/L, Total Dissolved Solids (TDS) 448.67-513.05 mg/L, Chloride (Cl-) 50.22-52.10 mg/L, Sulphate (SO₄²⁻)29.49-35.51 mg/L, Nitrate (NO₃⁻) 3.18-3.49 mg/L, and Turbidity 18.59-18.82(NTU), respectively. Pearson correlation coefficient values shows high, moderate and sometimes low significant positive and negative relationship (p<0.05 level). According to Water Quality Index (WQI), 57.637 for Dugda Ground water shows poor water quality status and 66.92 for Bhojudih Ground water also shows poor water quality status as per Water Quality Index standard rating.